Firm performance, innovation modes and territorial embeddedness - Nunes, S. (2015)
This paper seeks to identify different innovation modes and their territorial embeddedness, relating them to firms’ innovative and economic performance. We also analyze the relationship between the different innovation modes and the economic impact of the crisis on firms’ performance. These relationships are tested by regression and latent class models for the Portuguese population of firms, using a sample of 397 firms classified according to technological intensity, firm size and region. Our results show three different innovation modes: a DUI mode, a STI mode and a Territorial Embeddedness Innovation (TEI) mode in which the territory plays a key role. These innovative modes are related in different ways to firms' economic and innovative performance and also have marked distinctions in terms of resilience to the economic crisis. These findings lead to a reflection on the regional innovation policy in the European context.